MATHEMATICAL ANALYSIS WITH SYSTEMS "MATHEMATICS" AND WEB MATH (Conferencea, 2023)
We consider teaching the Continuous functions topic of Calculus using Mathematica and Web Mathematica. We show that it makes possible not only to visualize the traditional approach of teaching but helps the students to reach the deeper understanding of continuity. It is achieved by the best motivation and explication of mathematical concepts.